Essays on corporate fraud in Malaysian listed companies / Abdul Ghafoor - Abdul , Ghafoor (2018)
This thesis investigates the causes and consequences of corporate fraud in Malaysia. Three specific issues are examined in the Malaysian context through three interconnected essays. In the first essay, the thesis identifies key factors that elicit the fraudulent behavior of companies in Malaysia. Using enforcement action releases (EARs) issued by Securities Commission Malaysia (SC) and Bursa Malaysia as fraud sample for the period of 1996-2016, the study follows the framework of fraud triangle (i.e. pressure, opportunity, and rationalization) and Malaysian International Standards on Auditing (ISA) 240 to identify the factors. The findings of the first essay indicate that among variables proxied for the pressure variable, aggressive tax reporting, political connections, and financial distress significantly contribute to the fraud likelihood. The results of the variables used to capture opportunity suggest that dedicated institutional investors, independence of the board, effective audit committee, and presence of a female on the board provide active monitoring on the corporate board and are negatively associated with the likelihood of fraud commission. Moreover, the family firms with pyramidal ownership structure have high chances of fraud commission due to the expropriation of minority shareholders’ rights. Finally, regarding rationalization, this study finds that that prior violation, frequent changes of external auditors, and firm’s decision to switch to non-Big 4 auditors increase the chances of fraud occurrence. In the second essay, the study examines the changes in the simultaneity of corporate financial decisions (i.e., financing, investment, and dividend payouts) and the strength of interdependence among corporate decisions on fraud revelation. Using simultaneous equations (3SLS and 2SLS), the study documents that financing, investment, and dividends payouts of the fraudulent firms decrease following the revelation of fraud. In conformity with the flow of fund framework, the study provides evidence on the joint determination of corporate financing, investment, and dividend payouts decisions. Additionally, the study also finds the comprehensive support for the increase in strength of the simultaneity of corporate decisions in the periods following the fraud revelation. In the third essay, the study investigates the post-fraud behavior of fraudulent firms to restore the corporate legitimacy. For the purpose, the study considers the changes in management and governance turnover as ameliorating actions to improve the earnings quality. The results provide little support for the claim that fraudulent firms improve the earnings quality to restore the broken trust. Among various variables used as corrective actions, only the audit committee independence, its effectiveness, and audit quality show a significant effect on earnings quality. Overall, the results seem to indicate that fraudulent firms in Malaysia do not strive to improve the earnings quality which is considered as the significant source of information to signal future prospects of the company.